Aurel Kolnai's "War against the West" reconsidered - Bialas, Wolfgang 1954- HerausgeberIn (Routledge studies in fascism and the far right, 2019)
Part 1. Topics addressed in Kolnai's The War against the West -- Aurel Kolnai's comparison of national socialism and communism in the context of contemporary comparisons of dictatorships / Uwe Backes -- Nazism, Christianity and the development of political religion theory in Kolnai's "War against the West" reconsidered / Richard Steigmann-Gall -- Aurel kolnai's reflections on antisemitism in contemporary context / Micha Brumlik -- Part 2. Comparing Kolnai with contemporary attempts of coming to terms with Nazism -- Aurel Kolnai's The War against the West and British attempts to understand Nazism before the war / Dan Stone -- Aurel Kolnai's The War against the West and the American debate on Nazism / Michaela Hoenicke Moore -- Aurel Kolnai and Franz Neumann: normative criticism and structural analysis of national socialism / Rolf Zimmermann --